Influence of multi gradient modulus interface layer constructed by flexible PI nanolayer modified carbon fiber surface on the mechanical properties of epoxy based composites - Tiantian Li; Ge Yu; Weipeng Huang; Yiling Chen; Yanchao Zhu; Ce Liang (Journal of Materials Research and Technology)
Carbon fiber (CF)-reinforced epoxy resin (ER)-based composites are promising materials with many application prospects. However, the chemical inertness of the CF surface leads to poor interfacial bonding with the matrix, adversely affecting the mechanical properties, which are regarded as an insurmountable obstacle for their practical applications. Modifying the surface morphology of CFs to increase roughness and constructing a gradient modulus interface layer with rigid-flexible structures of polyimide (PI) on the CF surface to enhance the affinity between CFs and ER. Additionally, the multi-layer interface mitigates internal and external stress concentrations to improve the mechanical properties of the material. Notably, the addition of a flexible PI nanolayer significantly reduces the brittleness of epoxy-based composites, promoting ductile fracture. The reduced contact angle of CFs in polar and non-polar solutions after modification indicates that polydopamine (PDA) and highly polar PI enhance chemical compatibility at the composite interface, increasing the overall surface energy of the CF. Additionally, thermogravimetric analysis tests reveal that the excellent heat resistance of PI significantly enhances the thermal stability of the polymer on the modified CF surface. In conclusion, this work provides a feasible method for constructing novel gradient modulus interfacial layers with nanostructured rigid-flexible architectures in ER, offering new insights for designing next-generation advanced composites.